2015
DOI: 10.18632/oncotarget.4139
|View full text |Cite
|
Sign up to set email alerts
|

Increased resistance to proteasome inhibitors in multiple myeloma mediated by cIAP2 - implications for a combinatorial treatment

Abstract: Despite the introduction of new treatment options for multiple myeloma (MM), a majority of patients relapse due to the development of resistance. Unraveling new mechanisms underlying resistance could lead to identification of possible targets for combinatorial treatment. Using TRAF3 deleted/mutated MM cell lines, we evaluated the role of the cellular inhibitor of apoptosis 2 (cIAP2) in drug resistance and uncovered the plausible mechanisms underlying this resistance and possible strategies to overcome this by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…In vitro studies conducted on the issue have shown that administration of DEBIO 1143 together with bortezomib [20] or carboplatin [4] or radiation [21] or JQ1 [22] can induce apoptosis in various cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies conducted on the issue have shown that administration of DEBIO 1143 together with bortezomib [20] or carboplatin [4] or radiation [21] or JQ1 [22] can induce apoptosis in various cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…tir. LP-1 ve ANBL-6 multiple myeloma hücre hatlarında, AT-406'nın, proteazom inhibitörlerinden birisi olan bortezomibin (PS-341) antitümoral etkisini artırdığı bulunmuştur (19). AT-406'nın proteazom inhibitörlerinin NF-κB nükleer lokalizasyonunu engelleme aracılığıyla apoptozisin indüklenmesine karşı hücrelerin hassasiyetini arttırması tedavinin daha etkili olabileceği açısından önemlidir.…”
Section: At-406 Ve Kanserunclassified
“…46 Other E3-targeting anticancer pharmacological agents that are in preclinical/clinical trials include small molecules targeting the p53-MDM2 interaction, inhibitors of apoptosis proteins, SKP2, and the anaphase-promoting complex/ cyclosome. [47][48][49][50][51][52][53] Thus, E3 ligase-directed therapy is indeed a promising effective approach. In this respect, the HECT domain E3 ligases are attractive potential targets for anticancer intervention as they possess a catalytic site and directly catalyze substrate ubiquitination.…”
Section: Limitations Of Ptm Profilingmentioning
confidence: 99%